1992
DOI: 10.1111/j.1440-0960.1992.tb00081.x
|View full text |Cite
|
Sign up to set email alerts
|

Modern Treatment of Lymphoedema I. Complex Physical Therapy: The First 200 Australian Limbs

Abstract: Complex Physical Therapy (CPT) is discussed and its principles outlined. CPT involves: 1. skin care, 2. a special lymphatic massage, 3. compression bandaging and (later) garments, 4. special exercises which supplement the massage. CPT was used on 78 patients with postmastectomy lymphoedema (17 with Grade 1 and 61 with Grade 2). There were significant differences between the Grades. In the first four-week course the mean Grade 1 was reduced from 121% of normal to 107% (the mean change in the oedema was 103% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
2

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 88 publications
(47 citation statements)
references
References 4 publications
4
41
0
2
Order By: Relevance
“…The present study showed the greatest improvements in rolephysical (p=0.002) and general health (p=0.003). The trend toward increases in physical functioning and role-physical scores of functional status and mental and general health scores of well-being supports the theory that CDPT is beneficial for the physical, and psychological health of women with secondary lymphedema after gynecological cancer treatment 5,25,26) . Subjects expressed feeling more confident using their affected lower limb for activities of daily living, and some mentioned that they had returned to walking long distances, playing sports, performing housework and shopping after the decongestive phase.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…The present study showed the greatest improvements in rolephysical (p=0.002) and general health (p=0.003). The trend toward increases in physical functioning and role-physical scores of functional status and mental and general health scores of well-being supports the theory that CDPT is beneficial for the physical, and psychological health of women with secondary lymphedema after gynecological cancer treatment 5,25,26) . Subjects expressed feeling more confident using their affected lower limb for activities of daily living, and some mentioned that they had returned to walking long distances, playing sports, performing housework and shopping after the decongestive phase.…”
Section: Discussionsupporting
confidence: 63%
“…Lymphedema volume was calculated for each segment by utilizing the formula for a truncated cone: Volume =H (C 2 + Cc+ c 2 )/12, H =height, C =circumference of the top of the cone, c =circumference of the base of the cone. This method demonstrated excellent inter-and intra-observer reproducibility in comparison with water displacement, which is considered the gold standard 25,26) . Volumes for each segment were averaged and the reduction in lower limb circumference was calculated by the following formula with the unaffected limb used as a normal control for the affected limb (percentage excess volume; PCEV): PCEV =(affected volume -unaffected volume)/unaffected volume × 100.…”
Section: Methodsmentioning
confidence: 95%
“…Garment use for 20 hours per day and longer has been suggested. 1,5,11,12,24,25 Bertelli et al 23 have reported statistically significant reduction of edema in patients who wore garments for 6 consecutive hours per day. A multivariate analysis noted superior reduction in those women who had not had significant weight gain following treatment for breast carcinoma.…”
Section: Compression Garmentsmentioning
confidence: 98%
“…12 Manual lymphatic drainage has been reported to be effective when used in combination with other antiedema efforts, such as complex decongestive therapies, as well as in combination with an intermittent compression pump and complex decongestive therapies. Manual lymphatic drainage is a specialized, distinct form of massage, incorporating regional massage as well as treatment of the affected limb.…”
Section: Massage Therapiesmentioning
confidence: 99%
See 1 more Smart Citation